ROLE OF PLASTICS IN MODERN LIFE: BENEFITS, RISKS AND ENVIRONMENTAL CONSEQUENCES - Bhokare P. R.; Ingole R. N. (International Educational Journal of Science and Engineering, 2025)
Plastics play a central role in modern society owing to their versatility, durability, lightweight nature, and cost-effectiveness, making them essential across sectors such as packaging, healthcare, transportation, agriculture, and electronics. Their widespread utility has contributed significantly to economic growth and technological advancement. However, the exponential increase in plastic production and the prevalence of single-use items have led to substantial environmental and public health concerns. This paper provides a critical assessment of the dual nature of plastics by examining their societal benefits alongside the ecological and health risks associated with their life cycle. Drawing on insights from authoritative sources, including Plastics in Life and Environment and Plastic Waste Management: Issues, Solutions & Case Studies, the study evaluates patterns of plastic generation, waste composition, pollution pathways, and the impacts of plastics on soil quality, freshwater systems, marine environments, and human health. Current data indicate that India generates approximately 9.4 million tonnes of plastic waste annually, with only about 60% being recycled, while the remainder contributes to land contamination, water pollution, air quality deterioration, and microplastic proliferation. The findings underscore urgent needs for transitioning toward a circular plastic economy, strengthening waste management infrastructure, enforcing regulatory frameworks, and promoting behavioral shifts that support sustainable consumption and responsible plastic use.